In-situ strain localization analysis in low density transformation-twinning induced plasticity steel using digital image correlation. (April 2015) - Eskandari, M.; Yadegari-Dehnavi, M.R.; Zarei-Hanzaki, A.; Mohtadi-Bonab, M.A.; Basu, R.; Szpunar, J.A.
Abstract: The effect of deformation temperature on the strain localization has been evaluated by an adapted digital image correlation (DIC) technique during tensile deformation. The progress of strain localization was traced by the corresponding strain maps. The electron backscatter diffraction analysis and tint etching technique were utilized to determine the impact of martensitic transformation and deformation twinning on the strain localization in both elastic and plastic regimes. In elastic regime the narrow strain bands which are aligned perpendicular to the tension direction were observed in temperature range of 25 to 180 °C due to the stress-assisted epsilon martensite. The strain bands were disappeared by increasing the temperature to 300 °C and reappeared at 400 °C due to the stress-assisted deformation twinning. In plastic regime strain localization continued at 25 °C and 180 °C due to the strain-induced alfa-martensite and deformation twinning, respectively. The intensity of plastic strain localization was increased by increasing the strain due to the enhancement of martensite and twin volume fraction. The plastic strain showed more homogeneity at 300 °C due to the lack of both strain-induced martensite and deformation twinning. highlights: Effect of deformation mechanism by changing temperature on strain localization is investigated by digital image correlation. EBSD technique is served to validate deformation mechanism as well as microstructural evolution. Strain induced martensite as well as deformation twinning is activated in the present steel affecting strain localization.